Assessment Multiple intelligence to the football players , according to various lines of play ( defense - MF - attackers - AL-Naimi, Dargham J.; Kamel, Jalal; Taeeb, Nihad E. (Humanities Journal of University of Zakho, 2017)
Recognition of multiple intelligences the football players , according to club teams . , As well as Identify the type of intelligence that enjoyed by football players , according to lines of play . Limited research problem in answering the following questions : Does the football players Zkaouat multiple ? What kind of multiple intelligences with soccer players ? Does the type of intelligence that enjoyed by football players , according to their positions ? Was used descriptive analytical approach to reach the objectives of the research , representing the research community and appointed teams ( Erbil, Dohuk, Slimania and Zaxo Sports football Clubs) from the Elite League and numbered (88) players were used content analysis and personal interview and a measure of multiple intelligences as a means of gathering information, researchers concluded that the football players foot have multiple Zkaouat and enjoy different kinds of intelligences , according to their positions and lines where they play .